2017
DOI: 10.1007/s10456-017-9583-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of angiogenesis in microbe-regulated inflammatory and neoplastic conditions

Abstract: Commensal microbiota inhabit all the mucosal surfaces of the human body. It plays significant roles during homeostatic conditions, and perturbations in numbers and/or products are associated with several pathological disorders. Angiogenesis, the process of new vessel formation, promotes embryonic development and critically modulates several biological processes during adulthood. Indeed, deregulated angiogenesis can induce or augment several pathological conditions. Accumulating evidence has implicated the angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 131 publications
2
73
0
4
Order By: Relevance
“…As well as VEGF-A binding its orthosteric ligand binding site, allosteric interactions can occur at topographically distinct regions [ 99 ]. Allosteric homotypic interactions between VEGFR2 monomers at Ig-like D4, D5 and D7 are an additional step necessary for VEGFR2 activation [ 84 , 100 , 101 , 102 , 103 ], as designed ankyrin repeat protein inhibitors (DARPins) can sterically block these interactions and allosterically inhibit VEGFR2 activation [ 103 , 104 ]. Ligand binding leads to a conformational twist throughout the extracellular region of VEGFR2 reorienting distinct Ig-like domains, shown by electron microscopy [ 100 ], small angle X-ray scattering [ 101 ], and the full-length crystal structure of structurally related VEGFR1 [ 88 ].…”
Section: Vegfr2 Signallingmentioning
confidence: 99%
“…As well as VEGF-A binding its orthosteric ligand binding site, allosteric interactions can occur at topographically distinct regions [ 99 ]. Allosteric homotypic interactions between VEGFR2 monomers at Ig-like D4, D5 and D7 are an additional step necessary for VEGFR2 activation [ 84 , 100 , 101 , 102 , 103 ], as designed ankyrin repeat protein inhibitors (DARPins) can sterically block these interactions and allosterically inhibit VEGFR2 activation [ 103 , 104 ]. Ligand binding leads to a conformational twist throughout the extracellular region of VEGFR2 reorienting distinct Ig-like domains, shown by electron microscopy [ 100 ], small angle X-ray scattering [ 101 ], and the full-length crystal structure of structurally related VEGFR1 [ 88 ].…”
Section: Vegfr2 Signallingmentioning
confidence: 99%
“…For studying tumor angiogenesis, different approaches exist. A compilation of the currently used in vivo, ex vivo , and in vitro bioassays has been recently published as a collaborative work of some of the main experts in the angiogenesis field ( 15 ). Briefly, in vivo experimental models allow the study of mechanisms, kinetics, and dynamics in the context of a complex organism.…”
Section: Insight Into the Angiogenic Tumor Ecosystemmentioning
confidence: 99%
“…Having found that Mfn2 overexpression was beneficial to N2a cells in the setting of the TNFα-mediated inflammation microenvironment [40,41], we next looked at whether Yap, the downstream effector of Mfn2, was also involved in the survival of mouse neuroblastoma N2a cells. To this end, siRNA against Yap was transfected into Mfn2-overexpressed cells, and then cell viability was determined by the MTT assay.…”
Section: Knockdown Of Yap Abolishes the Protective Effect Of Mfn2 Ovementioning
confidence: 99%